2020
DOI: 10.1161/circulationaha.119.043594
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Participation in Cardiovascular Clinical Trials From 2010 to 2017

Abstract: Background: Cardiovascular disease is the leading cause of death among women worldwide, yet, women have historically been underrepresented in cardiovascular trials. Methods: We systematically assessed the participation of women in completed cardiovascular trials registered in ClinicalTrials.gov between 2010 and 2017, and extracted publicly available information including disease type, sponsor type, country, tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
182
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(195 citation statements)
references
References 12 publications
3
182
2
8
Order By: Relevance
“…Furthermore, a recently published systematic review studying the participation of women in 740 cardiovascular clinical trials with 862 652 participants showed that, although this has improved over the last decade, men still predominate majority of cardiovascular clinical trials. 37 Reporting sex-specific results from clinical trials is important to obtain more insight into potential sex differences of treatment benefit and medication tolerance. Therefore, novel approaches to the recruitment and enrollment process and novel trial designs are needed to ensure that sex-specific results may be meaningfully obtained and applied to clinical practice.…”
Section: Control Of Cardiometabolic Risk Factor Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recently published systematic review studying the participation of women in 740 cardiovascular clinical trials with 862 652 participants showed that, although this has improved over the last decade, men still predominate majority of cardiovascular clinical trials. 37 Reporting sex-specific results from clinical trials is important to obtain more insight into potential sex differences of treatment benefit and medication tolerance. Therefore, novel approaches to the recruitment and enrollment process and novel trial designs are needed to ensure that sex-specific results may be meaningfully obtained and applied to clinical practice.…”
Section: Control Of Cardiometabolic Risk Factor Levelsmentioning
confidence: 99%
“…Therefore, novel approaches to the recruitment and enrollment process and novel trial designs are needed to ensure that sex-specific results may be meaningfully obtained and applied to clinical practice. 37 Another possible explanation may be found in differences of cardiometabolic risk factor levels at treatment initiation. As discussed earlier, it has been hypothesized that cardiometabolic risk factors need to deteriorate further in women than men before they are diagnosed with overt T2D.…”
Section: Control Of Cardiometabolic Risk Factor Levelsmentioning
confidence: 99%
“…The representation of women in clinical CV trials has fluctuated over the past two decades, consistently remaining below 50% [25][26][27]. Studies investigating the representation of women in CV trials over the last decade have reported rates ranging from 33 to 38% [26,27].…”
Section: Representation Of Women Of Racial/ethnic Minority Backgroundmentioning
confidence: 99%
“…The representation of women in clinical CV trials has fluctuated over the past two decades, consistently remaining below 50% [25][26][27]. Studies investigating the representation of women in CV trials over the last decade have reported rates ranging from 33 to 38% [26,27]. A 2019 study evaluating cohort demographics in CV clinical trials published in three major journals (The New England Journal of Medicine, The Lancet, The Journal of the American Medical Association) found that enrollment of women was 21% between 1986 and 1990 and 33% between 2011 and 2015, with a statistically significant increasing trend in enrollment [27].…”
Section: Representation Of Women Of Racial/ethnic Minority Backgroundmentioning
confidence: 99%
See 1 more Smart Citation